2011
DOI: 10.1007/s00775-011-0825-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MtnE, the fifth metallothionein member in Drosophila

Abstract: Metallothioneins (MTs) constitute a family of cysteine-rich, low molecular weight metal-binding proteins which occur in almost all forms of life. They bind physiological metals, such as zinc and copper, as well as nonessential, toxic heavy metals, such as cadmium, mercury, and silver. MT expression is regulated at the transcriptional level by metal-regulatory transcription factor 1 (MTF-1), which binds to the metal-response elements (MREs) in the enhancer/promoter regions of MT genes. Drosophila was thought to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 47 publications
1
54
0
Order By: Relevance
“…In a previous study, we showed the inflammatory effects of pulmonary administered Ag ENPs, the same ENPs as used in this study, with infiltration of neutrophils and expression of the pro-inflammatory cytokine IL-1b (Smulders et al, 2014), a known inducer of MT gene expression (De et al, 1990). In addition MT production can also be up regulated via MTF-1 binding to metal-response elements in the promoter regions of MT genes as shown in the presence of Ag-ions in Drosophila (Atanesyan et al, 2011) In this study, we demonstrated that the administered Ag ENPs are partially or completely dissolved with chelation of the released Ag ions by MTs or other thiol-containing molecules. Furthermore, higher concentrations of the metals Fe and Cu were observed in the Agrich spots.…”
Section: Elementmentioning
confidence: 51%
“…In a previous study, we showed the inflammatory effects of pulmonary administered Ag ENPs, the same ENPs as used in this study, with infiltration of neutrophils and expression of the pro-inflammatory cytokine IL-1b (Smulders et al, 2014), a known inducer of MT gene expression (De et al, 1990). In addition MT production can also be up regulated via MTF-1 binding to metal-response elements in the promoter regions of MT genes as shown in the presence of Ag-ions in Drosophila (Atanesyan et al, 2011) In this study, we demonstrated that the administered Ag ENPs are partially or completely dissolved with chelation of the released Ag ions by MTs or other thiol-containing molecules. Furthermore, higher concentrations of the metals Fe and Cu were observed in the Agrich spots.…”
Section: Elementmentioning
confidence: 51%
“…The fruit fly Drosophila melanogaster is one of the most studied insects in the fields of genetics and molecular biology and not surprisingly many studies on MT has been carried out in this species. It has been found that D. melanogaster genome harbors a family of at least five expressed MT genes, codifying respectively for five MT isoforms MtnA-E [38]. The analysis of fruit fly interactome revealed that the Zn-loaded MtnA and MtnB interacted with peroxiredoxin, opening new perspectives on the role of MTs in the redox network [39].…”
Section: Unconventional Animalsmentioning
confidence: 99%
“…The numbers of MTs vary among different species. For example, Drosophila melanogaster has five MTs [21], but only a single MT has been identified in Orchesella cincta [15]. In the present study, two full-length MT cDNA sequences were obtained from the O. chinensis transcriptome database.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies have focused primarily on mammalian and aquatic organisms and plants [9]. Few studies have examined the interactions between MTs and metal ions in Diptera and Collembola insects [20], [21]. Little is currently known regarding the molecular characteristics and functions of MT genes in Orthoptera insects, especially grasshohper Oxya chinensis .…”
Section: Introductionmentioning
confidence: 99%